2017
DOI: 10.4208/cicc.2017.v5.n2.2
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Transfer and Photo-Deamination Reactive Mechanisms Studies of Amines Compounds

Abstract: The reference [J. Org. Chem. 2015, 80, 10817.10828] has reported that the Quinone Methides (QMs) that are of significant medicinal benefits in biological field can be generated via photo-deamination reaction. In this study, the density functional theory (DFT) and time-dependent DFT (TDDFT) methods have been carried out to investigate the reactive mechanisms of free amines compounds 1 and 3. The excited state hydrogen bonding strengthening mechanism has been demonstrated by analyses of frontier molecular orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Similar experimental results were obtained upon photolysis at 355 and 223.1 nm, demonstrating that the reaction rate decreases in the order 355 > 266 > 223.1 nm for the photolysis wavelengths and in the order cyclohexane ≈ acetonitrile > water for the type of solvent. Thus, it appears that the tautomeric hydrogen transfer process in DMMP occurs at lower excited states (i.e., S 2 , S 1 , and/or T n excited states), in agreement with previously reported ESIPT reaction systems due to the hydrogen-bonding chain between solute and solvents. …”
Section: Resultssupporting
confidence: 89%
“…Similar experimental results were obtained upon photolysis at 355 and 223.1 nm, demonstrating that the reaction rate decreases in the order 355 > 266 > 223.1 nm for the photolysis wavelengths and in the order cyclohexane ≈ acetonitrile > water for the type of solvent. Thus, it appears that the tautomeric hydrogen transfer process in DMMP occurs at lower excited states (i.e., S 2 , S 1 , and/or T n excited states), in agreement with previously reported ESIPT reaction systems due to the hydrogen-bonding chain between solute and solvents. …”
Section: Resultssupporting
confidence: 89%
“…These highly electronegative atoms interact through electrostatic and dispersive forces, which contributes to the formation of HBs. Many studies have shown that upon photoexcitation of HB systems, the donor and acceptor molecules reorganized due to the significant difference in charge distribution of different electronic states, which made for the occurrence of the excited-state intramolecular proton transfer (ESIPT) reaction. …”
Section: Introductionmentioning
confidence: 99%